Influences of different storage environments and packaging materials on the quality of the traditional Chinese health food Herba Menthae Haplocalycis. (March 2018) - Zhou, Wenju; Luo, Jiaoyang; Zhao, Lianhua; Zhao, Ming; Ouyang, Zhen; Yang, Meihua
Highlights: A UPLC method was applied to determine the non-volatile components in HMH. Storage conditions and package materials have the important impacts on the quality of HMH. Low temperature and humidity and ziplock bag are suitable for the storage of HMH. Abstract: Herba Menthae Haplocalycis (HMH) is a traditional Chinese health food that is commonly used in the food industry, as well as numerous other industries. As the demand for HMH is increasing dramatically, a greater number of people are paying close attention to the quality of HMH. In this paper, we describe the establishment of an effective ultra high performance liquid chromatography – photo diode array (UPLC-PDA) method to study the effect of different storage environments (low temperature and humidity, normal temperature and humidity, high temperature and humidity) and packaging materials (ziplock bags, braided bags, kraft paper) on the HMH quality. The results from this study demonstrated that storage environments and packaging materials both influence the quality of HMH. The contents of hesperidin, diosimin, diosmetin-7- O -β-d -glucopyranoside, didymin and buddleoside were significantly affected when stored under conditions with normal temperature and humidity ( P   <  0.05), high temperature and humidity ( P   <  0.05), braided bags ( P   <  0.05) and kraft paper ( P   <  0.05). In addition, mycotoxins (aflatoxin B1, aflatoxin B2 and ochratoxin) were found in the food, which was also found to affect the quality. However, the contents of caffeic acid, rosmarinic acid, and diosimin were determined to be unaffected by the low temperature and humidity ( P   >  0.05) and ziplock bag storage ( P   >  0.05). Furthermore, we found that the contents of the eight components were decreased less at low temperature and humidity and in ziplock bags, compared to other storage environments and packaging materials. In addition, no mycotoxins were detected. These results indicate that low temperature and humidity and ziplock bag storage conditions are beneficial for maintaining HMH quality. This present study may provide a scientific basis for the quality control and establishment of novel storage specifications for HMH.